HUBUNGAN ANTARA VARIABEL AKUNTANSI DAN RETURN SAHAM DENGAN BETA SEBAGAI VARIABEL INTERVENING - AGUSTIN PALUPI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of this research is to analyze Beta (systematic risk) as an intervening variable between accounting variables (Dividend Payout Ratio, Assets Growth, Firm Size, Liquidity, Financial Leverage, Earnings Variability and Accounting Beta) and share return of companies listed at the Indonesia Stock Exchange. Data employed in this study was pooled data during the period of 2001 till 2005 which consist of 624 firm-years. The analysis tools used in this research is structural equation model (SEM). The results of this research show that Beta acts as an intervening variable between Dividend Payout Ratio, Firm Size and Financial Leverage and share return. Whiles the other accounting variables (assets growth and earnings variability) have direct effect on the stock return. Evidence in small firms indicates that certain factors have direct influence to investing decision such as firm size, earnings variability and accounting Beta. The test also suggests that Beta affect relation between dividend payout ratio, firm size and leverage and share return. This research finds no support for the role of liquidity and accounting Beta neither directly to return no intervened by Beta. The whole result is consistent with the proposition that Beta has important role in investing decision besides accounting information.